2003
DOI: 10.1002/chin.200328222
|View full text |Cite
|
Sign up to set email alerts
|

(+)‐Strigol, a Witchweed Seed Germination Stimulant, from Menispermum dauricum Root Culture.

Abstract: Other natural productsOther natural products U 0800 (+)-Strigol, a Witchweed Seed Germination Stimulant, from Menispermum dauricum Root Culture. -(YASUDA, N.; SUGIMOTO*, Y.; KATO, M.; INANAGA, S.; YONEYAMA, K.; Phytochemistry 62 (2003) 7, 1115-1119; Arid Land Res. Cent., Tottori Univ., Koyama, Tottori 680, Japan; Eng.) -Lindner 28-222

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…6) Yasuda et al have recently isolated strigol from an aseptic root culture of Menispermum dauricum DC., a Chinese medicinal, non-host plant. 7) Strigol is therefore produced by both host and non-host plants. In contrast to strigol, all of the other natural strigolactones characterized to date have only been isolated from host plants: sorgolactone from sorghum, 8) alectrol from cowpea, 9) and orobanchol from red clover.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6) Yasuda et al have recently isolated strigol from an aseptic root culture of Menispermum dauricum DC., a Chinese medicinal, non-host plant. 7) Strigol is therefore produced by both host and non-host plants. In contrast to strigol, all of the other natural strigolactones characterized to date have only been isolated from host plants: sorgolactone from sorghum, 8) alectrol from cowpea, 9) and orobanchol from red clover.…”
mentioning
confidence: 99%
“…For example, according to the estimate by Yasuda et al, they recovered only 2% of strigol originally present in a culture filtrate, the greatest loss occurring during the ODS-HPLC separation. 7) In the previous paper, a simple and rapid analytical method for known strigolactones using HPLC-tandem mass spectrometry (LC/MS/MS) was reported.…”
mentioning
confidence: 99%
“…In the following years, the SL orobanchol was isolated from red clover (Yokota et al 1998), sorgomol from sorghum (Xie et al 2008b), and 5-deoxystrigol from L. japonicus (Akiyama et al 2005), sorghum, maize, pearl millet (Awad et al 2006), and several Fabaceae species . Many other SLs from host plants and root exudates of the nonhost plant white lupin or root culture of Menispermum dauricum (Yasuda et al 2003) were reported. According to the proposed SL biosynthetic pathway (Matusova et al 2005), 5-deoxystrigol might be a common precursor for SL.…”
Section: Strigolactones As Signal Molecules Of Parasitic Weedsmentioning
confidence: 97%
“…2). 12,27,[29][30][31][32][33][34][35] Although strigolactones are perhaps more widely distributed in the plant kingdom, the isolation and characterization of strigolactones in root exudates have been hampered by the extremely low concentrations produced and exuded by host roots and by their relative instability. Analysis using high-performance liquid chromatography (HPLC) connected to tandem mass spectrometry indicated the presence of several novel strigolactones, including one strigol isomer, two dehydro-strigol isomers, and four tetradehydro-strigol isomers, in the root exudates of soybean, carrot, tomato, sorghum, and pea.…”
Section: Strigolactones Act As the Host-derived Signal Branching Fmentioning
confidence: 99%